2016
DOI: 10.1007/s11356-016-6875-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in water, sediment and three fish species from the Danube River, Serbia: a cause for environmental concern

Abstract: The aim of this study was to investigate the presence of metal contamination in water, sediments and three different fish species. All samples were taken from the Danube River in Belgrade Region, a location upstream from Grocka. Concentrations of Cd, Hg and Pb in water samples were not detected, while concentrations of Zn, Fe, Cu and As were in the range of 0.004-0.41 mg L(-1). Iron was the most deposited metal in sediment samples (17,530.00 mg kg(-1)). For the purpose of heavy metal determination in fish tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…On the contrary, the mean Cd values in muscle of S. glanis obtained in the study were higher than those obtained by Jovicic et al [13] in the same species from Danube River, Serbia. The mean Cd values in liver and muscle of S. glanis obtained in the study were higher than those obtained by Ivanovic et al [14] in the same species from Danube River, Serbia. The mean Cd values in liver and muscle of S. glanis obtained in the study were higher than those obtained by Milanov et al [15] in the same species from Danube River, Serbia.…”
Section: Discussioncontrasting
confidence: 78%
“…On the contrary, the mean Cd values in muscle of S. glanis obtained in the study were higher than those obtained by Jovicic et al [13] in the same species from Danube River, Serbia. The mean Cd values in liver and muscle of S. glanis obtained in the study were higher than those obtained by Ivanovic et al [14] in the same species from Danube River, Serbia. The mean Cd values in liver and muscle of S. glanis obtained in the study were higher than those obtained by Milanov et al [15] in the same species from Danube River, Serbia.…”
Section: Discussioncontrasting
confidence: 78%
“…Lead damages and destroys erythrocytes; reduces resistance; weakens the bones; blocks the nervous system; inhibits the absorption of iodine, necessary for correct functioning of the thyroid gland; forms toxic deposits in the organism, causing numerous disorders and diseases, [41]; 0.053-0.7396, 0.0195-0.0489 [18]; 0.07-0.22 [72]; <LOQ-1.14 [17]; 0.0001-0.0003 [52]; 0.0378-0.5243 [73]; 0.60-0.62 [74]; 0.088-0.410, [43]; 0.005-1.17 [39], * 0.140-0.327 in d.w. [75], * 0.094-0.466 [76], * 0.16-0.53 [77] 0.50 and 1.0 (tuna) [26] As Cd 0.0033-0.0754 0.0046-0.0720 [16]; 0.002-0.07 [78]; 1.00-1.80 [66]; 0.08-0.66 [41]; 0.0-53.9 [18]; 0.019 [79]; <LOQ-0.09 [17]; 0.08 [36]; 0.0032-0.0834 [73]; 0.020-0.025 [74]; <LOQ-0.007 [39]; 0.03-0.12 [37]; <LOQ-0.18 [40]; 0.19-17.05 [80], * 0.008-0.191 in d.w. [75], * 0.021-0.082 [76], * 0.01-0.21 [77] 0.050 and 0.10 (sardine, tuna) [26] Pb 0.011-0.296 0.0126-0.0726 [16]; 0.007-0.51 [78]; 3-4.60, 3.60-4.00 [66]; 0.14-0.92 [41]; 0.02-1.37 [35]; 0.0-31.1 [18]; 0.11 [79]; <LOQ-4.13 [17]; 0.10 [36]; <LOQ-3.19, 0.35-2.10, 0.25-1.51 in d.w. [42]…”
Section: Comparison With Reported Literature Values and Withmentioning
confidence: 99%
“…Non-essential metals such as Cd, Hg, Ni and Pb have no biological function and are toxic even at low concentrations (Ivanović et al 2016). Our results showed that trace metal bioaccumulation varied significantly among tissues.…”
Section: Discussionmentioning
confidence: 69%